Dynamiken politischer Imagination : die deutschsprachige Utopie von Stifter bis Döblin in ihren internationalen Kontexten, 1848-1930 - Leucht, Robert (Studien und Texte zur Sozialgeschichte der Literatur, 2016)
"The study traces the history of utopias from 1848 to 1930 as settings for competing political visions and the impact of utopias on changing social realities. This re-evaluation of utopias also offers promising insights about a universal problem in cultural studies - namely, the relationship between literature and politics. What stories must be told to inspire people toward a better world?"--